Assembly of gold nanorods functionalized by zirconium-based metal–organic frameworks for surface enhanced Raman scattering. Issue 14 (28th March 2022) - Li, Juan; Liu, Zhenfeng; Tian, Dehua; Li, Baojun; Shao, Lei; Lou, Zaizhu
Abstract : Assembly of gold nanorods functionalized by zirconium-based metal–organic frameworks (Au nanorod@Zr-MOF) for superior SERS detection. Abstract : Surface-enhanced Raman scattering (SERS) is a promising detection technique providing outstanding molecular fingerprint identification and high sensitivity of analytes. Developing sensitive and stable SERS substrates is highly desirable but remains a challenge. We herein report a wet-chemistry approach for the preparation of (Au nanorod core)@(Zr-based metal–organic framework shell) (Au nanorod@Zr-MOF) nanostructures with the Zr-MOF shell thickness ranging from 3 nm to 90 nm. The stacked Au nanorod@Zr-MOF composites exhibit remarkably improved SERS sensitivity because the MOF shell enriches the molecules to the abundant plasmonic hotspots between the Au nanorod cores. The optimized Au nanorod@Zr-MOF structures exhibit superior SERS activity for detecting 4′-mercaptobiphenylcarbonitrile molecules at a concentration as low as 2 × 10 −10 M, with the SERS enhancement factor 2 and 8 times as high as that of ordered bare Au nanorod arrays and random stacking bare Au nanorods, respectively. This study enriches the library of hybrid nanostructures of plasmonic nanocrystals and MOFs, providing an integrated SERS platform with molecular enrichment capability for the realization of sensitive and quantitative analyte identification.